Dismantling inequities to end the black maternal mortality crisis in the United States - Ameneh Safarzadeh (International Journal for Equity in Health)
Abstract Black maternal mortality in the United States remains alarmingly high—Black women are still more than three times as likely to die from pregnancy-related causes than White women. This crisis is not due to individual choices or access alone, but to deeply rooted structural inequities, including systemic racism, policy exclusion, and the neglect of Black-led care models. While efforts like Medicaid expansion and the Black Maternal Health Momnibus Act aim to address these gaps, they often fall short by relying on narrow, one-size-fits-all solutions. This commentary uses Critical Health Equity theory and the Intersectionality-Based Policy Analysis (IBPA) framework to examine how current policies may unintentionally reinforce the very inequities they seek to eliminate. It argues that achieving real equity in maternal health requires more than reform—it calls for a fundamental shift in who holds power, whose knowledge is valued, and how care is delivered. A new framework is proposed that centers Black leadership, supports community-led research, and promotes culturally safe, justice-oriented care.